Analisis Keuntungan Dan Titik Impas (Break Even Point) Industri Rumah Tangga Tahu Di Kecamatan Punggur - Muhammad Zaini; Sutarni Sutarni; Teguh Budi Trisnanto (Politeknik Negeri Lampung, 2007)
The gool of this research is to calculate the total of cost, total of revenue and advantage of effort, determining amount of tired output time and of condition BEP, determining influence of price change of output and input to amount output and assess the BEP, and also determine the amount produce the minimum and price sell normal. Research at home industry in Sidorahayu Punggur Lampung Tengah with the method survai.Â Result of research indicate that the mean produce the soybean cake reach 8.919,53 cutting per day, at the price of selling soybean cake of mean Rp 71,18,- per cutting, Advantage obtained in home industry know equal to Rp 1.913.343,98,- per month, with the total expense equal to Rp 17.373.060,38,-. per month. Condition BEP reached at the time of home industry productive soybean cake equal to 96.080,23 cutting per month, and sell the output of equal to Rp 6.838.849,77 per month. If producer wish the profit of equal to 30 % from total expense hence minimum sale have to reach 630.088,23 cutting per month or Rp 44.832.406,43 per month. Price sell normal if producer wish the profit 30% total expense equal to Rp 84,40,00. If input price go up 15 % and price output remain to hence home industry at condition do not profit.Â Kata Kunci:Â Pedapatan, Titik Impas, Industri rumahtangga